Analysis of RANS turbulence models by calculating the steady-state flow in the Turbine-99 draft tube - Sentyabov, Andrey Vasilievich; Gavrilov, Andrey Anatolievich; Dekterev, Aleksander Аnatolievich; Minakov, Andrey Viktorovich (Computational Continuum Mechanics, 2013)
Numerical simulation of the flow in the Turbine-99 draft tube is presented. Axisymmetric inlet boundary conditions were used for steady state simulation. Modern RANS turbulence models, implemented in the CFD package SigmaFlow, were considered for simulation of the swirling flow in a hydraulic power plant. The investigation confirms the validity of the proposed numerical methods for calculating the stationary flow.
Keywords: computational fluid dynamics; swirling flow; turbulence models; hydro turbine; draft tube